Poultry blood from slaughterhouses: development of a biopreservation system to improve microbiological quality prior to transforming blood into by-products - Zbrun, María Virginia (2016)
The aim of this study was to investigate the use of indigenous lactic acid bacteria (LAB) with specific additives as a Biopreservation System (BS) for poultry blood during its storage in slaughterhouses. The BS consisted of two LAB (Enterococcus faecalis DSPV 008SA or Lactobacillus salivarius DSPV 032SA) with 4 additives (lactose 2 g/l, yeast extract 0.4 g/l, ammonium citrate 0.4 g/l and NaCl 1 g/l). After 24 h storage at 30ºC, lower counts of enterobacteria, coliforms, Pseudomonas spp. and Staphylococcus aureus were evident in blood treated with the BS than in untreated blood. The ability of LAB to prevent haemolysis was evident. A decrease in pH was associated with control of spoilage microorganisms but it needed to be regulated to prevent coagulation of proteins. On the basis of these results it is recommended to supplement blood with a BS to avoid undesirable changes during blood storage before processing.